Churches, Blackness, and Contested Multiculturalism
IX, 294 p. 1 illus.
Keywords: This volume assesses contemporary church responses to multicultural diversity and resisted categories of social difference, with a central focus on whether or how racial, ethnic, religious, sexual, and gender differences are validated by churches (and especially black churches) torn between competing inclusive and exclusive tendencies.